Menyudahi Analogi Antropomorfisme: Mendamaikan Biologi, Sosiologi, dan Psikologi melalui Psikogenealogi Antropologi Kedaulatan Negara - Hizkia Yosie Polimpung (Antropologi Indonesia, 2011)
It is quite often, wittingly or unwittingly, that people assume society, even the state, as person. They talk about society in a way as if it shares same attributes with human being: can be sick (as if it has body), can think (as if it has mind), can speak (as if it has mouth), for example. It is quite obvious that this gesture implies a view of society as an agglomeration of individuals. The problem arises around the legitimacy of this gesture: namely, to analogize the society as individuals always implies a logical leap. Things even get murkier when this gesture is applied even more to the way in which people recognize the state: as collectivities, as a “big-person.” This gesture, which has methodological impact, is what the author call ‘anthropomorphism analogy’. By doing what the author call psychogenealogy—a mixture of Lacanian psychoanalysis and Foucauldian genealogy, that is a way at seeing history as constituted by various contestation of materialization of desire—to the history of the modern state, namely, modern sovereign state, the author seeks to remedy this analogy with an objective account. The purpose is not to side with the analogy, but to prove that it is invalid not because it is scientifically inadequate, but that it is a true correspondence: state is person. Keywords: Anthropomorphism analogy, state, sovereignty, psychogenealogy, desire, anxiety